Development of a human melanoma organoid-containing skin-on-a-chip model for in vitro drug testing and personalized medicine - Feil Yang; Bochong Shi; Jiapeng Zhao; Xueqiang Liu; Jing Zhang; Zhonghang Wang; Xianglin Hu; Chao Liang; Mo Cheng; Wei Sun; Yu Xu; Zhongze Gu; et al. (Biofabrication, 2026)
Abstract Melanoma, an aggressive and lethal form of skin cancer, poses significant challenges in treatment because of its complex biological mechanisms and poor therapeutic response. However, the construction of biomimetic in vitro models of melanoma with organs-on-a-chip micro-environment have not been reported. This study aimed to design and biofabricate a novel melanoma-containing skin-on-a-chip model for the evaluation of drug responses, and to investigate the effects of ultraviolet (UV) irradiation on melanoma progression. Our results demonstrated pronounced heterogeneity in the tumor immune microenvironment of melanoma patients. The melanoma organoids derived from patients effectively preserve the native immune components, and organoids retained both the histological features and genetic characteristics of the original tumors. Drug response assessments indicated that the combination of dabrafenib and trametinib significantly inhibited melanoma cell proliferation and induced apoptosis; while UV exposure significantly promoted melanoma progression, highlighting the role of environmental factors in tumor development. Our research suggested the biofabrication of a biomimetic melanoma organoid-containing skin-on-a-chip model could elucidate patients’ specific melanoma biology, tumor immune microenvironment, and corresponding drug sensitivity.